Regulation of Neisseria meningitidis cytochrome bc1 components by NrrF, a Fur‐controlled small noncoding RNA. Issue 9 (5th August 2017) - Pannekoek, Yvonne; Huis in 't Veld, Robert; Schipper, Kim; Bovenkerk, Sandra; Kramer, Gertjan; Speijer, Dave; van der Ende, Arie
Abstract : NrrF is a small regulatory RNA of the human pathogen Neisseria meningitidis . NrrF was previously shown to repress succinate dehydrogenase ( sdhCDAB ) under control of the ferric uptake regulator (Fur). Here, we provide evidence that cytochrome bc 1, encoded by the polycistronic mRNA petABC, is a NrrF target as well. We demonstrated differential expression of cytochrome bc 1 comparing wild‐type meningococci and meningococci expressing NrrF when sufficient iron is available. Using a gfp ‐reporter system monitoring translational control and target recognition of sRNA in Escherichia coli, we show that interaction between NrrF and the 5′ untranslated region of the petABC mRNA results in its repression. The NrrF region essential for repression of petABC was identified by site‐directed mutagenesis and is fully conserved among meningococci. Our results provide further insights into the mechanism by which Fur controls essential components of the N. meningitidis respiratory chain. Adaptation of cytochrome bc 1 complex component levels upon iron limitation is post‐transcriptionally regulated via the small regulatory RNA NrrF. Abstract : NrrF is a small regulatory RNA of the human pathogen Neisseria meningitidis which is differentially expressed when encountering low iron concentrations in the host. This research provides insights into mechanisms by which NrrF downregulates essential N. meningitidis respiratory chain components, reducing the need for their iron cofactors.